Cohousing - social impacts and major implementation challenges. - Hacke, Ulrike; Müller, Kornelia; Dütschke, Elisabeth (Oekom, 2019)
Local networks are in decline, and housing is growing increasingly expensive. These are but a few of the current challenges in the field of housing. One possible solution is cohousing projects: these form local communities, create affordable housing, and contribute to a sustainable economy. Nevertheless, diffusion of cohousing remains slow. Transforrning the housing sector is possible only os part of a larger political or social movement.
Keywords: Wohnen; Gemeinschaftswohnen; Mehrgenerationenwohnen; Wohnform; Wohnprojekt; Sozialbeziehung; Nachbarschaft; Fallbeispiel